Tailings from Fundão Tragedy: Physical–Chemical Properties of the Material That Remains by Candonga Dam. (10th January 2020) - Figueiredo, Marina Duarte; Lameiras, Fernando Soares; Ardisson, José Domingos; Araujo, Maria Helena; Teixeira, Ana Paula de Carvalho
ABSTRACT: In this work, samples of Fe mining tailings from the collapsed Fundão Dam, Brazil, which were retained by the Candonga hydroelectric power plant, were characterized by various techniques. Quartz, hematite, kaolinite, and goethite were identified as the main phases present. The composition, homogeneity, and relatively low ( 1%) organic matter content indicate potential for usage of these tailings in civil constructions. The next step of this work is to investigate such applications. If their feasibility is confirmed, the goal is to use this material for construction in the areas affected by the Fundão Dam rupture. This use will lead to positive socio‐environmental impacts in these regions, where tailings still need to be removed and damaged infrastructure needs to be repaired. Integr Environ Assess Manag 2020;16:636–642. © 2019 SETAC KEY POINTS: Our study characterizes Fe tailings deposited near the Candonga hydroelectric power plant dam, in Doce River (Minas Gerais, Brazil). The material analyzed presents good homogeneity and its main phases are quartz, hematite, kaolinite, and goethite. The tailings are classified as nondangerous, noninert, noncorrosive, and nonreactive. The results indicate potential for usage of tailings in cement‐based materials for civil construction. RESUMO: Neste trabalho, amostras do rejeito de mineração de ferro, proveniente do rompimento da barragem de Fundão e retidas pela usina hidroelétrica de Candonga, foram caracterizadas por diversas técnicas. Quartzo, hematita, caulinita e ghoetita foram identificadas como as principais fases presentes no rejeito. A composição, homogeneidade e teor de matéria orgânica relativamente baixo, cerca de 1%, indicam uso potencial deste material em construção civil. O próximo passo deste trabalho é investigar tais aplicações. Se a viabilidade for confirmada, o objetivo é utilizar esse material para obras nas áreas afetadas pelo rompimento da barragem de Fundão. Isso contribuirá para reduzir os impactos socioambientais nessas regiões, as quais ainda necessitam da remoção do rejeito e de reparos na infraestrutura danificada. Integr Environ Assess Manag 2020;16:636–642. © 2019 SETAC